Association of age at menopause and type 2 diabetes: A systematic review and dose-response meta-analysis of cohort studies. Issue 4 (August 2019) - Guo, Chunmei; Li, Quanman; Tian, Gang; Liu, Yu; Sun, Xizhuo; Yin, Zhaoxia; Li, Honghui; Chen, Xu; Liu, Xuejiao; Zhang, Dongdong; Cheng, Cheng; Liu, Leilei; et al.
Highlights: The first dose-response meta-analysis to evaluate the association between age at menopause and T2DM. Six high-quality cohort studies were included in this meta-analysis. Restricted cubic spline model was used to fit and an inverse linear association between the variables was observed. Abstract: Aims: Early age at menopause has been associated with increased incidence of type 2 diabetes mellitus (T2DM), but the quantitative association between age at menopause and T2DM was unclear. We performed a meta-analysis to assess the dose-response association between age at menopause and T2DM. Methods: PubMed, Embase and Web of Science were searched up to January 5, 2019 for cohort studies that evaluated the association of age at menopause and risk of T2DM. Relative risks (RRs) and 95% confidence intervals (95% CIs) were pooled by using the random-effects models. Restricted cubic spline model was used to evaluate the liner or nonlinear relation. Results: We identified 6 studies for the meta-analysis (267, 284 women and 19, 654 cases of T2DM). The pooled RR was 0.64 (95% CI 0.44–0.94) comparing the latest with the earliest category of age at menopause. The risk of T2DM was reduced by 10% (RR = 0.90, 95% CI, 0.84–0.98) with each 5-year increment in age at menopause. We found an inverse linear association between age at menopause and T2DM. Conclusions: Our results suggest that later age at menopause was associated with lower risk of T2DM.